Textbook: a dialogical analysis of the integrative project covers - Silva, Anderson; Marfori, Maria Aparecida (Seven Editora, 2023)
This investigation problematizes the existing dialogical relationships between the covers of the Integrator Project – Languages area textbooks, highlighting the points of consonance and dissonance, as well as the relationship with the various parameterizing educational documents. Thus, this research is justified by the current change in the National Textbook Program for Secondary Education, including the inclusion of books from the Integrator Project for the choice of public schools. Moreover, this investigation has as a theoretical-methodological framework the contributions of Dialogical Discourse Analysis (DDA), in which we list concrete utterances and dialogic relations as categories of analysis. In organizational terms, this work is divided into three moments: a) presentation of the new National Textbook Program (PNLD), in which we will focus on the public notice, the Guide of the National Program of Digital Textbook and other related documents to the engendering of the corpus; b) synthesis of the theoretical contribution, presenting the key concepts for the readings and discussions; c) contrastive analysis of the listed covers, based on the dialogical bias of language. In our final considerations, the elements of the analyzed covers were organized to persuade and induce choice, enunciating dialogical relationships consonant with the educational documents in force. DOI: https://doi.org/10.56238/methofocusinterv1-029